Pengaruh Model Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematika Pada Siswa Kelas VII SMPN 154 Jakarta - Sri Susanti; Maya Nurfitriyanti (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this research is to analyze whether there were influence of using Realistic Mathematic Education (RME) learning model on the mathematics problem solving ability of the student class VII SMPN 154 Jakarta. The method used is a quasi method experiments with post test only design is the design used to identify the effects of RME learning model on student’s mathematics problem solving ability after given special treatment and controlled. Based on the result of hypotheses  test with t test, it showed that t test = 2. 835 and t table = 2.025 in significance level at 5 % or ? = 0.05, it means ttest> ttable (2.835 > 2.025), so H0 was rejected and H1 Was accepted, and there are significant impacts of RME on mathematics problem solving ability.